Personal nouns in -ist in Danish vs. -ist(a) and -yst(a) in Polish - Rajnik, Eugeniusz (Folia Scandinavica Posnaniensia, 2007)
The paper deals with the word-formation analysis of Danish personal nouns in -ist and their formal counterparts in -ist/a/ and yst/a/ in Polish. The analysis is based on Bzdęga’s binary model. The Danish suffix -ist is usually tacked on to nouns though some deadjectival derivatives can also be found. Some personal nouns with the above suffixes have parallel forms with the same meaning. Some Danish personal nouns in -ist have no Polish equivalents though there exist relevant bases in Polish. Numerous Polish derivatives in -ist/a / and -yst/a/ are rendered by compounds in Danish.